Culture and Business: How Can Cultural Psychologists Contribute to Research on Behaviors in the Marketplace and Workplace? - Masuda, Takahiko; Ito, Kenichi; Lee, Jinju; Suzuki, Satoko; Yasuda, Yuto; Akutsu, Satoshi (Frontiers in Psychology, 2020)
Cultural psychology has great potential to expand its research frameworks to more applied research fields in business such as marketing and organizational studies, while going beyond basic psychological processes to more complex social practices. In fact, the number of cross-cultural business studies have grown constantly over the past 20 years. Nonetheless, the theoretical and methodological closeness between cultural psychology and these business-oriented studies has not been fully recognized by scholars in cultural psychology. In this paper, we briefly introduce six representative cultural constructs commonly applied in business research, which include (1) individualism vs. collectivism, (2) independence vs. interdependence, (3) analytic vs. holistic cognition, (4) vertical vs. horizontal orientation, (5) tightness vs. looseness, and (6) strong vs. weak uncertainty avoidance. We plot the constructs on a chart to conceptually represent a common ground between cultural psychology and business research. We then review some representative empirical studies from the research fields of marketing and organizational studies which utilize at least one of these six constructs in their research frameworks. At the end of the paper, we recommend some future directions for further advancing collaboration with scholars in the field of marketing and organizational studies, while referring to theoretical and methodological issues.